Implementation of Regulations on Fire Hazard Prevention and Mitigation in Wetland Environmental Areas in Banjarmasin City - Firdaus*, Muhammad Ananta; Indrawan, Rudy; Firdaus, Ahmad Fitra; Wilyati, Wilyati (Riwayat: Educational Journal of History and Humanities, 2023)
Banjarmasin City, as the city center in South Kalimantan Province, faces a serious threat from fire risk. Its geographical and climatic conditions make it vulnerable to catastrophic fires, especially during the dry season. In an effort to overcome this challenge, the city government has taken strategic steps in the form of Banjarmasin City Regional Regulation No. 13 of 2008 concerning Fire Hazard Prevention and Control, and established the Fire and Rescue Service (Damkar) in 2022. This research uses socio-legal research methods that combine normative and sociological approaches. Qualitative analysis methods are used to explore deep insights into normative aspects related to fire disaster prevention and management. This interdisciplinary approach allows for a more holistic understanding of the issue, involving both legal and social aspects. Fire disasters not only threaten residential areas, but also vacant land. Therefore, fire prevention and suppression must be carried out effectively and efficiently. Protection against fire hazards includes the use of extinguishing equipment such as sprinklers, fire hydrants, and detectors, as well as building design planning that minimizes fire risk. However, more important are prevention efforts that include education, evacuation, and early handling when a fire occurs. The importance of legal protection for the community in dealing with fire risk is the main focus. This is reflected in the local regulations formed and the improvement efforts made. The role of Damkar in fire disaster management became central, and the meeting between the Regional Government and the Self-Help Fire Brigade Front (BPK) became a strategic step in coordinating these efforts. The revision of Banjarmasin City Regional Regulation No. 13 of 2008 and Banjarmasin Regional Regulation No. 23 of 2012 are concrete efforts in perfecting the legal framework governing fire disaster prevention and management. Thus, the city government strives to protect its people through effective and efficient measures, and encourages active participation from various parties in maintaining mutual safety and welfare